Soviet Legacy in the Operation of Pasture Governance Institutions in Present-Day Kyrgyzstan - Aiganysh Isaeva; Jyldyz Shigaeva (Revue de Géographie Alpine)
The paper looks at the Soviet legacy in pasture governance systems of Kyrgyzstan that reproduce Soviet-era practices, meanings and power hierarchies. The study focuses on the current operation of local-level institutions (Pasture Users Associations and Pasture Committees) and the changing role of herders as a key pasture user category in the new socio-economic environment. Path dependence theory, which posits that old institutions continue to structure new policy arrangements, frames the analysis. Empirical data collected in Kyrgyzstan’s Naryn Province show how non-participatory decision-making and implementation modes, as well as the meanings surrounding pasture use, that were shaped during the Soviet era, still influence institutions in the present day, along with established patterns amongst resource users and between resource users and their environment.